2007
DOI: 10.17221/2241-pps
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium spp. In wheat grain in the Czech Republic analysed by PCR method

Abstract: A complex of Fusarium spp. causes Fusarium head blight (FHB) on wheat and also on barley. Infection with FHB results not only in yield loss, but also causes depreciation of the harvested product due to the accumulation of toxins such as deoxynivalenol produced by Fusarium spp. The flowering time is a very susceptible period for primary infection. One reason might be that during this period spores can get into the opened wheat florets where they may later cause infection.Initial symptoms of infection of a wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…1). A similar trend was observed in Poland (Stepień et al 2008), Czech Republic (Nedělník et al 2007), Austria (Adler et al 2002), the Netherlands (Waalvijk et al 2003). One explanation could be mono-cultivation of wheat, minimizing tillage (Lukanowski & Sadowski 2002) and growing of maize as a forecrop, crop residues of maize are the main source of F. graminearum.…”
Section: Resultssupporting
confidence: 66%
“…1). A similar trend was observed in Poland (Stepień et al 2008), Czech Republic (Nedělník et al 2007), Austria (Adler et al 2002), the Netherlands (Waalvijk et al 2003). One explanation could be mono-cultivation of wheat, minimizing tillage (Lukanowski & Sadowski 2002) and growing of maize as a forecrop, crop residues of maize are the main source of F. graminearum.…”
Section: Resultssupporting
confidence: 66%
“…Harvested products are contaminated due to the accumulation of toxins such as deoxynivalenol (DON) produced by Fusarium spp. (Nedělník et al, 2007). Mean grain contamination rates did not exceed the permitted limit norms (1.25 mg/kg = limit for contamination according to EC Regulation No.…”
Section: Hulled Wheat Speciesmentioning
confidence: 93%
“…A large number of species from the genus Fusarium are involved in FHB's development, but the most frequent and most significant of these are F. graminearum, F. culmorum, F. avenaceum, and F. poae (Bai *Corresponding author;Phone: +420 573 317 113 and Shaner 1994; Nicholson et al 2003;Landschoot et al 2012). The species F. grami nearum and F. culmorum are predominant within the Czech Republic (Nedělník et al 2007;Váňová et al 2008). The most recent studies across Europe have indicated a rising proportion of F. poae (Audenaert et al 2009;Lindblad et al 2013).…”
Section: Introductionmentioning
confidence: 99%